2012
DOI: 10.1016/j.juro.2011.09.061
|View full text |Cite
|
Sign up to set email alerts
|

Benign Prostate Specific Antigen Distribution and Associations With Urological Outcomes in Community Dwelling Black and White Men

Abstract: Purpose To describe the cross-sectional associations of benign prostate-specific antigen (BPSA) with clinical urologic measures, and to examine the risk of future urologic outcomes in two population-based cohorts of black and white men. Materials and Methods Two population-based, cohort studies were established to characterize the natural history and risk factors for progression of prostate disease in white and black male residents of Olmsted County, Minnesota and Genesee County, Michigan, respectively. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 25 publications
0
10
2
Order By: Relevance
“…The modest age-adjusted correlations between changes in BPSA and [-2]proPSA levels and changes in symptoms and maximum flow rate are consistent with the correlations among annual changes in urologic measures previously reported in this same cohort 24,25 . Additionally, cross-sectionally, the associations between BPSA level and presence of lower urinary tract symptoms or depressed urinary flow rate were much lower than the associations with an enlarged prostate 10 .…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The modest age-adjusted correlations between changes in BPSA and [-2]proPSA levels and changes in symptoms and maximum flow rate are consistent with the correlations among annual changes in urologic measures previously reported in this same cohort 24,25 . Additionally, cross-sectionally, the associations between BPSA level and presence of lower urinary tract symptoms or depressed urinary flow rate were much lower than the associations with an enlarged prostate 10 .…”
Section: Discussionmentioning
confidence: 72%
“…However, as baseline BPSA level increases with increasing age group, absolute levels of BPSA over time will increase across age groups. We had previously found that baseline levels of BPSA were associated with future BPH treatment and diagnosis of CaP 10 . While changes in BPSA levels over time were slightly higher for men who developed an enlarged prostate or CaP, these differences were not significant.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…BPSA is closely related to prostate volume and does not appear to have any prognostic capacity in terms of distinguishing potentially indolent from aggressive disease [12]. Although serum BPSA alone is unlikely to differentiate between hyperplasia and cancer, in combination with assays for [−2]proPSA, it may allow additional discrimination [13,14]. Intact PSA comprises an additional free PSA subset that has been identified as a potential predictive serum biomarker [15].…”
Section: Options For Prostate Cancer Screening In 2015mentioning
confidence: 99%